A child's garden of verses - Stevenson, Robert Louis, 1850-1894.; Tudor, Tasha (Chicago : Rand McNally, 1981)
A collection of poems evoking the world and feelings of childhood.
Children's Catalog (Wilson)
4.7
K-3
Keywords: Children's poetry, Scottish; Scottish poetry; English poetry